2020
DOI: 10.21037/jtd.2020.03.103
|View full text |Cite
|
Sign up to set email alerts
|

miR-107 inhibited malignant biological behavior of non-small cell lung cancer cells by regulating the STK33/ERK signaling pathway in vivo and vitro

Abstract: Background: The role of miRNAs in non-small cell lung cancer (NSCLC) has been broadly studied and confirmed, and miR-107 has attracted an ever-growing level of attention. This study set out to research the mechanism of the effect of miR-107 on the malignant biological behavior of NSCLC in vivo and vitro.Methods: The expression of miRNAs related to the development of NSCLC was detected by RT-qPCR. Western blotting was carried out to detect expression levels of serine/threonine kinase 33 (STK33) and proteins rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…On the 28 th day of injection, mice were euthanized by neck dislocation, and the xenografts were harvested, photographed, and weighed. 35 …”
Section: Methodsmentioning
confidence: 99%
“…On the 28 th day of injection, mice were euthanized by neck dislocation, and the xenografts were harvested, photographed, and weighed. 35 …”
Section: Methodsmentioning
confidence: 99%
“…Especially, miR-107 could serve as an important downstream effector for lncRNAs or circRNAs in NSCLC [ 3 ]. As for key targets of miR-107, BDNF, CDK6, FGFRL1, and STK33 were confirmed in vitro and in vivo [ 13 , 27 29 ]. In our study, we showed Wnt3a was the crucial target of miR-107, which enriched our understanding of how miR-107 inhibited invasion and EMT of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies revealed that miRNAs regulated tumor proliferation, invasion, and EMT by downstream genes [ 12 ]. miR-107 was recently shown to play a tumor-suppressive role in various cancers, including CRC and NSCLC [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, miR-107 expression demonstrated a decrease in NSCLC, and the augment of miR-107 oppressed the ferocious performance of cancer cells through the modi cation of its downstream actor cyclin-dependent kinase 6 [31]. An experimental exploration has detected that overexpressing miR-107 damaged the malignant phenotype of NSCLC cells partially by serine/threonine kinase 33-meidated extracellular regulated protein kinases pathway [32]. Amazingly, hsa-miR-107, once sponged by lncRNA FYVE, RhoGEF and PH domain containing 5 antisense RNA 1, indirectly offered a niche for NSCLC cells to proliferate [33].…”
Section: Discussionmentioning
confidence: 99%